America's Strategic Shift From Terrorism to Neoterism In Confronting With Iran Based On Arrogant Other Making - جلیل دارا; mahdi hosaini (Faṣlnāmah-i Pizhūhish/hā-yi Rāhburdī-i Siyāsat, 2019)
Jewish fundamentalism, as a kind of a variety of religious fundamentalism, has its own specifics, while having similarities to other forms of fundamentalism. Different interpretations of religious and historical sources have led to the formation of various forms of Jewish fundamentalism, which, if we want to provide an indicator for categorizing these species, is the best indicator of the "exile" or "return" principle. From the perspective of the fundamentalists that we are in exile or the time of return, we have our own rules and requirements, and on this basis we can mention three fundamental types of fundamentalism: passive fundamentalism, pragmatic fundamentalism, and promised believing fundamentalism. The Jewish fundamentalists, while dividing into different groups, have the same ultimate goals, and the difference between the aforementioned species is a tool, method, and time-space detection. Of course, in addition to the intra-religious components, the alignment or opposition to political movements, the role played by the policies of the Zionist regime, and also the attention to the adoption of pragmatic positions of some of these groups, one can well categorize and why certain positions in different types of fundamentalism Explaining.